Single-crystalline FeCo nanoparticle-filled carbon nanotubes: synthesis, structural characterization and magnetic properties - Ghunaim, Rasha; Klingeler, Rüdiger (Beilstein journal of nanotechnology, 2018)
In the present work, we demonstrate different synthesis procedures for filling carbon nanotubes (CNTs) with equimolar binary nanoparticles of the type Fe–Co. The CNTs act as templates for the encapsulation of magnetic nanoparticles and provide a protective shield against oxidation as well as prevent nanoparticle agglomeration. By variation of the reaction parameters, we were able to tailor the sample purity, degree of filling, the composition and size of the filling particles, and therefore, the magnetic properties. The samples were analyzed by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), superconducting quantum interference device (SQUID) and thermogravimetric analysis (TGA). The Fe–Co-filled CNTs show significant enhancement in the coercive field as compared to the corresponding bulk material, which make them excellent candidates for several applications such as magnetic storage devices.
Gesehen am 05.04.2019